Estimated Taxation Method in the Saudi Income Tax Law (The International Journal for Scientific Research, 2024)
The thesis delves into the complex realm of the Estimated Taxation Method within the Saudi Income Tax Law, offering a comprehensive analysis of this crucial aspect of taxation. The study aims to fill a significant gap in the existing literature by providing a detailed examination of the legal framework surrounding estimated taxation and the challenges faced by taxpayers in Saudi Arabia. Through a meticulous review of primary and secondary sources, including law review articles and academic documents, the thesis employs deductive reasoning to scrutinize the regulatory framework governing estimated taxation. By focusing on the specific context of Saudi Arabia, the research sheds light on the uncertainties and ambiguities introduced by the expansive discretion granted to the tax authority in imposing estimated taxation. The significance of this study extends beyond academic discourse, as it aims to provide valuable insights for foreign investors considering investments in the Kingdom of Saudi Arabia. It gives a preamble to foreigners seeking to invest in the fast-growing economy of Saudi Arabia.  In other words, the research seeks to enhance clarity, consistency, and adequacy in the regulatory framework governing taxation. It achieves this by offering a nuanced understanding of the Estimated Taxation Method and its implications for taxpayers. Overall, this thesis contributes to the ongoing dialogue on tax laws and income tax, emphasizing the need for a well-defined regulatory framework that balances the interests of taxpayers and the tax authority. In sum, by addressing a novel aspect of taxation not previously explored in published research, this study enriches the understanding of tax policies and their impact on economic activities in Saudi Arabia.
Keywords: Estimated Taxation Method; Saudi Income Tax Law; Saudi Arabia Taxpayers; Regulatory Framework; Taxation Practice